The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1101/707711
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermodynamic and Kinetic Characterization of Protein Conformational Dynamics within a Riemannian Diffusion Formalism

Abstract: We have formulated a Riemannian framework for describing the geometry of collective variable spaces of biomolecules within the context of collective variable based molecular dynamics simulations. The formalism provides a theoretical framework to develop enhanced sampling techniques, path-finding algorithms, and transition rate estimators consistent with a Riemannian treatment of the collective variable space, where the quantities of interest such as the potential of the mean force, minimum free energy path, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…There have also been attempts to include the orientational degrees of freedom ,, and to consider the transient subdiffusive mode. , Apart from mass transport, there have been attempts to describe, for example, the kinetics of proteins and biocomplexes . It has also been suggested that the position-dependent diffusion constant can be used to eliminate the ambiguity related to the choice of reaction coordinates in interpreting the PMF. , …”
Section: Introductionmentioning
confidence: 99%
“…There have also been attempts to include the orientational degrees of freedom ,, and to consider the transient subdiffusive mode. , Apart from mass transport, there have been attempts to describe, for example, the kinetics of proteins and biocomplexes . It has also been suggested that the position-dependent diffusion constant can be used to eliminate the ambiguity related to the choice of reaction coordinates in interpreting the PMF. , …”
Section: Introductionmentioning
confidence: 99%
“…Other possibilities considered include, for example, a “tilt” of MerF into the membrane plane, which may expose MerF's Cys21/22 to the periplasm. The true reaction coordinate, which typically is a concerted motion of the protein(s), likely involves all of these simpler descriptors . Thus, our choice of variables to bias may limit the physical relevance of the obtained free energies.…”
Section: Discussionmentioning
confidence: 99%
“…This second quantity has also been termed the Riemannian effective potential. 54,55 Several papers have laid out the very subtle differences in these two definitions, 17,54 with an examination of the coarea formula being perhaps the clearest way to see the relationship. 17 The derivatives of both quantities can still be related to the mean force along the collective variable, with proper corrections for changes of variables which are beyond the scope of this summary.…”
Section: Theory: Fes Estimation From Biasedmentioning
confidence: 99%
“…The “geometric FES”, in contrast, is defined as where Σ­(ξ⃗) is the surface of constant ξ⃗, and dΩ is the phase space volume of this surface, and thus is the logarithm of probability density of the surface Σ­(ξ⃗). This second quantity has also been termed the Riemannian effective potential. , Several papers have laid out the very subtle differences in these two definitions, , with an examination of the coarea formula being perhaps the clearest way to see the relationship . The derivatives of both quantities can still be related to the mean force along the collective variable, with proper corrections for changes of variables which are beyond the scope of this summary. , …”
Section: Theory: Fes Estimation From Biased Sampled Datamentioning
confidence: 99%